Immunomodulatory Treatment Strategies Targeting B Cells for Heart Failure - Zhang, Xinxin; Sun, Yuxi; Wang, Ning; Zhang, Yanli; Xia, Yunlong; Liu, Ying (Frontiers in Pharmacology, 2022)
Cardio-oncology, a nascent specialty, has evolved as a concerted strategy to address the cardiovascular complications of cancer therapies. On the other hand, emerging evidence has shown that some anti-tumor drugs, such as CD20-targeted rotuximab, also have markedly cardioprotective effects in addition to treating cancers. Rituximab is a CD20-targeted monoclonal antibody and kill tumor B-cells through antibody-mediated and antibody-independent pathways, indicating that B cells participate and promote the progression of cardiovascular diseases. In this review, we mainly present the evidence that B cells contribute to the development of hypertrophy, inflammation, and maladaptive tissue remodeling, with the aim of proposing novel immunomodulatory therapeutic strategies targeting B cells and their products for the treatment of heart failure.